A pocket philosophical dictionary - Voltaire 1694-1778 (Oxford, [U.K.] Oxford University Press, 2011)
"Here is the only available English translation of one of the landmarks of European Enlightenment thought, Voltaire's 1764 edition of A Pocket Philosophical Dictionary. Highly entertaining and still highly relevant, the "dictionary" actually consists of a sequence of short essays, arranged in alphabetical order, covering everything from Apocalypse and Atheism to Tolerance and Tyranny. The unifying thread of these articles is Voltaire's vitriolic critique of established religion: ridicule of established dogma, attacks on superstition, and pleas for toleration. Witty and ironic, this is very much a work of combat, part of Voltaire's high-profile political struggle in the 1760s to defend the victims of religious and political intolerance. This new translation is based on the definitive French edition of 1764 that provoked widespread controversy and condemnation. In his Introduction Nicholas Cronk considers the nature of Voltaire's engagement in political debate, literary style, contemporary reaction, the lasting impact of the work and its continuing relevance to debates on religious intolerance. The volume also includes an up-to-date bibliography and full explanatory notes."--Publisher.
Introduction -- Note on the text -- Note on the translation -- Select bibliography -- A chronology of Voltaire -- A Pocket Philosophical Dictionary -- Appendix : Two portraits of Voltaire in 1764 -- Explanatory notes.
"First published as an Oxford world's classics paperback 2011"--Title page.
Keywords: Liberty of conscience; Dogmatism; Political science -- Philosophy